FROM OVERSIGHT TO ACCOUNTABILITY: EVALUATING INTERNAL GOVERNMENT SUPERVISION USING THE CIPP MODEL - Arsad, Muhammad; Noor, Irwan; Hidayati, Firda (Erudio Journal of Educational Innovation, 2026)
Strengthening accountability in local government requires internal oversight that not only complies with regulations but also drives tangible improvements in governance performance. This study applies the Context, Input, Process, and Product (CIPP) evaluation model to assess how the Blitar Regency Inspectorate supports development accountability. The analysis covers institutional capacity, resource readiness, oversight procedures, and the use of audit results in performance management. The findings indicate that although oversight mechanisms and formal procedures are established, their impact is constrained by limited human resources, weak coordination with planning and budgeting units, and inconsistent follow up on recommendations. As a result, internal oversight has not yet fully translated into stronger development planning and performance accountability. The study concludes that strengthening institutional capacity, improving the follow up process, and better integrating oversight outputs into the broader performance management system are essential to ensure that internal oversight contributes more effectively to accountable, results oriented local governance.